Design and Simulation of High-Yield Dimethyl Ether Synthesis Using Series Reactors and Intercooler - Saffanah Azka Nurfiana; Fairuz Zahirah Shofa; Larasati Larasati; Yuri Dayita; Salsabila Cahyaningsih (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Dimethyl ether (DME, CH₃OCH₃), the simplest alkyl ether and a structural isomer of ethanol, has attracted considerable attention as a clean fuel and chemical intermediate. To enhance its production efficiency, process modifications were introduced and rigorously evaluated through simulation modeling. The methodology involved systematic optimization of operating parameters to achieve targeted performance criteria. A key innovation was the adoption of a series-reactor configuration integrated with an intercooler between reactors, designed to improve conversion and yield. The modified process demonstrated a substantial improvement in DME production, with yield increasing from 40.87% to 62.29%. These results confirm that the proposed process modification significantly augments both yield and conversion, thereby offering a more efficient and sustainable route for DME synthesis. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).